Analysis of the Effects of Light Emitting Diode (LED) Phototherapy on the Hematological and Biochemical Parameters of Rabbits Using Repeated Measures Longitudinal ANOVA (Jurnal Matematika, Statistika dan Komputasi, 2026)
This study examined the longitudinal effects of Light Emitting Diode (LED) phototherapy on hematological (hemoglobin) and biochemical (creatinine) parameters in rabbits (Oryctolagus cuniculus). Although LED phototherapy is widely applied as a non-invasive treatment, its systemic effects in repeated-measure settings remain limited. Fourteen rabbits were randomly assigned to a control group (n = 7) and a treatment group (n = 7). The treatment group received two 12-hour LED phototherapy sessions on consecutive days, while the control group underwent identical conditions without LED activation. Hemoglobin and creatinine levels were measured at three time points and analyzed using Repeated Measures ANOVA, with assumption testing for normality, homogeneity, and sphericity; Greenhouse–Geisser correction was applied when necessary. The results showed that observation time significantly affected hemoglobin (p = 0.004967) and creatinine levels (p = 0.03577), indicating temporal physiological changes that occurred regardless of treatment exposure. However, no significant differences were observed between the control and treatment groups for hemoglobin (p = 0.936) or creatinine (p = 0.357), and no significant group–time interaction was detected, suggesting that the observed changes were independent of LED phototherapy. Post-hoc pairwise comparisons based on estimated marginal means (EMMs) with Tukey adjustment revealed a significant increase in hemoglobin from time 0 to time 1 and a significant difference in creatinine between time 1 and time 2, further supporting that these variations reflect natural physiological processes rather than treatment-induced effects. These findings indicate a lack of evidence of treatment effect under the studied conditions, although the relatively small sample size warrants cautious interpretation. Future studies with larger samples are recommended.
Keywords: LED Photography; Hematological; Biochemical; Repeated Measures ANOVA; Rabbit Model